An Analysis Of EFL Students’ Difficulties In Speech Perception: A Qualitative Study On Misheard Minimal Pairs - Waruwu, Puspa Triyani; Tafonao, Yunita; Waruwu, Merlin; Gulo, Arniwati; Harefa, Afore Tahir (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
Perception of speech is a fundamental skill in EFL learning that is very challenging for Indonesian learners due to the limitations of their L1 vocal system. Although previous studies have mostly used quantitative accuracy measurements, qualitative exploration of authentic experiences in the classroom is still limited, especially for university-level EFL students in the context of psycholinguistics. This study investigates the difficulties of fifth-semester English Education students at Nias University in perceiving minimal vowel pairs through a descriptive qualitative design. Data from 15 purposive sampling participants were collected through a minimal pairs listening test (20 items), semi-structured interviews, and classroom observations. The results show the highest error rates of 87% for /ɪ/–/iː/ (ship-sheep) and 80% for /ʊ/–/uː/ (full-fool), caused by the Indonesian vowel system, which has only five monophthongs without length/tension contrast. Internal factors included L1 phonological interference and cognitive load, while external factors included poor classroom audio quality and environmental noise. Students relied more on context-based top-down strategies than bottom-up phonetic analysis. These findings reveal patterns of vowel perception difficulties characteristic of Indonesian EFL in an authentic learning context.